Beneficiary dependence on the South African Working for Water Programme : a multi-site case study of four projects in the Western Cape - Hough, Jan Anton (Stellenbosch : University of Stellenbosch, 2010)
Thesis (MA (Sociology and Social Anthropology))--University of Stellenbosch, 2010.